E-220 Patient-specific hemodynamics predict outcomes after treatment of intracranial aneurysms with flow-diverting stents. (4th August 2020) - Lim, D; March, L; Barbour, M; Haughn, H; Levy, S; Prijoles, K; Bass, D; Barros, G; Kelly, C; Chassagne, F; Aliseda, A; Levitt, M; et al.
Abstract : Introduction: Despite advancements in endovascular treatment of intracranial aneurysms, up to 30% recur and require additional treatment. Predicting outcomes after aneurysm treatment with flow-diverting stents (FDS) could impact treatment strategy and avoid unnecessary follow-up. Computational fluid dynamics (CFD) techniques have been used to simulate the effect of treatment on the intracranial aneurysm hemodynamics, and to quantify change in certain hemodynamics factors that can be associated with treatment success or failure. We use CFD simulations, based on aneurysm anatomy and patient-specific blood flow and pressure data, to study which hemodynamics factors are predictive of six-month treatment outcomes. Materials and Methods: Twenty-four patients with n=25 unruptured intracranial aneurysms treated with FDS were included (Table 1 ). 3-dimensional rotational angiographic anatomy was used to create the computational model and intraoperative blood velocity and blood pressure measurements proximal to the aneurysm, obtained with an endovascular dual-sensor microwire, were used as boundary conditions for CFD simulations before and after FDS treatment. For post-treatment calculations, a virtual stent based on the Pipeline Flex Embolization Device was deployed into the CFD simulations. Hemodynamics factors within the aneurysm dome including flow into aneurysm (Q), wall shear stress (WSS), wall shear stress gradient (WSSG), viscous dissipation, oscillatory shear index (OSI), and relative residence time (RRT) were calculated before and after FDS placement. Aneurysm treatment was classified as success or failure based on six-month follow-up angiography. Hemodynamics changes between immediate post-treatment and pre-treatment simulations were associated to treatment outcomes. Results: Marked reduction in Q, WSS, WSSG, and OSI were seen in most cases immediately after FDS treatment compared to the pretreatment values, indicative of the redirection of blood flow along the neck plane. Reduction of Q at peak systole and increase in RRT in the aneurysm dome were strong predictors of FDS treatment success. Further multivariate analysis of hemodynamic predictors of treatment outcome will be presented. Conclusion: Patient-specific CFD simulations using intraoperative physiological velocity and pressure data have been performed pre- and immediately post-treatment. Hemodynamics factors have the potential to predict aneurysm treatment outcomes, making them valuable for neurointerventionalists to consider in treatment planning. Disclosures: D. Lim: None. L. March: None. M. Barbour: None. H. Haughn: None. S. Levy: None. K. Prijoles: None. D. Bass: None. G. Barros: None. C. Kelly: None. F. Chassagne: None. A. Aliseda: None. M. Levitt: 1; C; Philips Volcano. L. Kim: None.